The Holistic Animal Handbook : A guidebook to nutrition, health, and communication - Solisti-Mattelon, Kate.; Mattelon, Patrice (Tulsa, Okla. : Council Oak ; Enfield : Airlift [distributor], 2004)
'The Holistic Animal Handbook' combines practical information about diet, nutrition and training with animal communication and emotional balancing techniques. It guides readers in helping their companion animals themselves and encourages cooperation with vets, trainers, and healthcare practitioners.
Previous ed.: U.S.: Beyond Words, 2000.
Includes bibliographical references and index.
Keywords: Pets -- Nutrition; Pets -- Health; Human-animal communication; Holistic veterinary medicine; Farming and Country Life